Modeling the diffusion of D-2-hydroxyglutarate from IDH1 mutant gliomas in the central nervous system. Issue 9 (5th April 2018) - Linninger, Andreas; Hartung, Grant A; Liu, Benjamin P; Mirkov, Snezana; Tangen, Kevin; Lukas, Rimas V; Unruh, Dusten; James, C David; Sarkaria, Jann N; Horbinski, Craig
Abstract: Background: Among diffusely infiltrative gliomas in adults, 20%–30% contain a point mutation in isocitrate dehydrogenase 1 (IDH1 mut ), which increases production of D-2-hydroxyglutarate (D2HG). This is so efficient that D2HG often reaches 30 mM within IDH1 mut gliomas. Yet, while up to 100 µM D2HG can be detected in the circulating cerebrospinal fluid of IDH1 mut glioma patients, the exposure of nonneoplastic cells within and surrounding an IDH1 mut glioma to D2HG is unknown and difficult to measure directly. Methods: Conditioned medium from patient-derived wild type IDH1 (IDH1 wt ) and IDH1 mut glioma cells was analyzed for D2HG by liquid chromatography–mass spectrometry (LC-MS). Mathematical models of D2HG release and diffusion around an IDH1 mut glioma were independently generated based on fluid dynamics within the brain and on previously reported intratumoral and cerebrospinal D2HG concentrations. Results: LC-MS analysis indicates that patient-derived IDH1 mut glioma cells release 3.7–97.0 pg D2HG per cell per week. Extrapolating this to an average-sized tumor (30 mL glioma volume and 1 × 10 8 cells/mL tumor), the rate of D2HG release by an IDH1 mut glioma (SA ) is estimated at 3.2–83.0 × 10 −12 mol/mL/sec. Mathematical models estimate an SA of 2.9–12.9 × 10 −12 mol/mL/sec, within the range of the in vitro LC-MS data. In even the most conservative of these models, the extracellular concentration of D2HG exceeds 3 mM within a 2 cm radius from the center of an IDH1 mut glioma. Conclusions: The microenvironment of an IDH1 mut glioma is likely being exposed to high concentrations of D2HG, in the low millimolar range. This has implications for understanding how D2HG affects nonneoplastic cells in an IDH1 mut glioma.